2019
DOI: 10.3390/molecules24173158
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Block Copolymer PCL-PEG-PCL as Stationary Phase for Capillary Gas Chromatographic Separations

Abstract: This work presents the first example of utilization of amphiphilic block copolymer PCL-PEG-PCL as a stationary phase for capillary gas chromatographic (GC) separations. The PCL-PEG-PCL capillary column fabricated by static coating provides a high column efficiency of 3951 plates/m for n-dodecane at 120 °C. McReynolds constants and Abraham system constants were also determined in order to evaluate the polarity and possible molecular interactions of the PCL-PEG-PCL stationary phase. Its selectivity and resolving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Peaks at 1.40–1.65, 2.32, and 4.06 ppm were assigned to methylene protons of −(CH 2 ) 3 –, −OCCH 2 –, and −CH 2 OOC– in the PCL units, respectively. The sharp peak at 3.65 ppm was attributed to methylene protons of −CH 2 CH 2 O– in PEG units of block copolymers . The acetal bond formation was confirmed by the characteristic peaks at 4.7–4.8 ppm assigned as methine protons of acetal groups and at 1.3 ppm from methyl protons of acetal groups.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Peaks at 1.40–1.65, 2.32, and 4.06 ppm were assigned to methylene protons of −(CH 2 ) 3 –, −OCCH 2 –, and −CH 2 OOC– in the PCL units, respectively. The sharp peak at 3.65 ppm was attributed to methylene protons of −CH 2 CH 2 O– in PEG units of block copolymers . The acetal bond formation was confirmed by the characteristic peaks at 4.7–4.8 ppm assigned as methine protons of acetal groups and at 1.3 ppm from methyl protons of acetal groups.…”
Section: Resultsmentioning
confidence: 84%
“…The sharp peak at 3.65 ppm was attributed to methylene protons of −CH 2 CH 2 O− in PEG units of block copolymers. 22 The acetal bond formation was confirmed by the characteristic peaks at 4.7−4.8 ppm assigned as methine protons of acetal groups and at 1.3 ppm from methyl protons of acetal groups. The very weak peaks at 4.23 ppm were attributed to methylene protons of −O−CH 2 − in the PEG end-unit linked with the PCL blocks.…”
Section: Resultsmentioning
confidence: 92%
“…PCL-PEG-PCL stationary phase has a linear structure, which has been reported by our group. 30 As shown, the Star-PEG-PCL 2 column can separate almost all analytes except 2,6-dimethylphenol/2-ethylhexanoic acid (peaks 9/10) and dicyclohexylamine/methyl dodecanoate (peaks 11/12), showing its excellent resolving capability for the complex mixture. Regarding the retention behavior, the Star-PEG-PCL 2 column exhibited distinct elution order compared to other comparative columns.…”
Section: 1 Grob Test Mixturementioning
confidence: 80%
“…[23,24] In our previous works, the triblock copolymers including PCL-PDMS-PCL and PCL-PEG-PCL found that the improving chromatographic performance originated from the addition of PCL block. [25][26][27] However, as with most hydroxy terminated polymeric materials, the relatively low thermal stability of PCL necessitates its functionalization.…”
Section: Introductionmentioning
confidence: 99%